An additional simultaneous magnetic ordering and magneto-capacitive behavior with dielectric relaxation besides multiferroicity in Fe1−xTexVO4. (29th March 2023) - Bera, Ganesh; Surampalli, Akash; Prajapat, Deepak; Mal, P; Reddy, V R; Kumar, Kranti; Sagdeo, Archna; Das, Pradip; Turpu, G R
Abstract: Here we report the evidence of an additional magnetic ordering and frequency dispersive magneto-dielectric (MD) permittivity besides multiferroic behavior in Te 4+ ( S = 0) doped FeVO4 . Two antiferromagnetic transitions similar to FeVO4 at ∼21.86 K (T N 1 ) and 16.03 K (T N 2 ) were observed in all samples. An additional novel defect clusters based magnetic ordering at relatively higher temperature (T A M O ) ∼ 203 K is also observed from the magnetization. Evaluated magnetic moments show systematic decrease and the magnetic frustration factors show an increase with the increasing of Te 4+ ( S = 0) content. MD studies show stable ferroelectric ordering at spiral magnetic transition (T N 2 ) and the multiferroic order persists to the largest doping of Te ( x = 0.10). The MD studies also reveal a magneto-capacitive (MC) behavior at T A M O (∼203 K) with a high dielectric constant and loss, and the possible reason for the magnetic ordering and MC behavior is ascribed to short range magnetic clustering arising out of defect based mechanisms. Mössbauer spectroscopic studies confirm local structural correlation with magnetic and ferroelectric ordering.